Pencil Grip X-Ray View Improves Detection of Early Wrist Arthritis - Abola, Matthew V.; Dearden, Marissa E.; Reddy, Kartik I.; Amen, Troy B.; Lee, Steve K. (Journal of Wrist Surgery, 2025)
Long-term sequelae of scapholunate instability predictably result in progressive arthritic changes. In early stages of arthritis, joint space narrowing, subchondral sclerosis, and osteophytic formation can be difficult to appreciate on posterior–anterior (PA) X-ray views of the wrist. In patients with scapholunate advanced collapse (SLAC) wrist, the pencil grip X-ray may more accurately define the joint space narrowing in the radioscaphoid and radiolunate articulations compared with standard PA radiographs.We conducted a retrospective chart review of all patients with pencil grip X-ray views and documented wrist arthritis at a single institution. A total of 29 patients met criteria. Two authors independently reviewed wrist X-rays and classified the X-rays based on radiographic stages of arthritis for both PA and pencil grip X-rays. Radioscaphoid and radiolunate joint spaces were measured, and mean comparisons were performed using student's t-test, and boxplot comparisons were calculated for each arthritis grade.In direct comparison of joint space narrowing, the radioscaphoid distance observed on the pencil grip radiographs was significantly lower than the PA wrist view in all arthritis grades (p < 0.05). The pencil grip view demonstrated more accurate joint space narrowing in patients with grade 2 osteoarthritis, but, not in other grades. There were no differences in radiolunate distance between pencil grip and PA wrist X-rays in all arthritis grades.The pencil grip X-ray view demonstrated significantly lower radioscaphoid distances across all arthritis grades compared with PA views, suggesting it may be more sensitive in detecting joint space narrowing. In particular, the pencil grip view more accurately demonstrated radioscaphoid joint space narrowing with grade 2 osteoarthritis. No significant differences were found in radiolunate distances between the two imaging methods.This study highlights the potential of the pencil grip X-ray view as a valuable tool for more accurately assessing early radioscaphoid wrist arthritis.
Keywords: osteoarthritis; pencil-grip; X-ray imaging